Odpowiedzi

2009-12-15T16:17:30+01:00
Najlepsza Odpowiedź!
2009-12-15T16:38:23+01:00
V₁=4/3*π*r₁³
V₂=4/3*π*r₂³
r₁=2r₂
324 π = 4/3*π*r₁³ + 4/3*π*r₂³
324 π = 4/3*π*(2r₂)³ + 4/3*π*r₂³
324 π = π (4/3*8r₂³+4/3*r₂³ )= π (32/3r₂³ + 4/3r₂³)
324 π = π 36/3r₂³ /:π
324=12r₂³ /:12
27 = r₂³ / ³√
r₂=3cm

r₁=2r₂
r₁=2 *3
r₁=6cm

V₁=4/3*π*r₁³ =4/3*π*6³=4/3*216*π=288π cm³-objętość I kuli

V₂=4/3*π*r₂³ =4/3*π*3³=4/3*27*π=36π cm³-objętość II kuli
1 5 1
2009-12-15T16:55:49+01:00
V₁= 4/3*π*r₁³
V₂= 4/3*π*r₂³

V₁+ V₂= 324π
4/3*π*r₁³ + 4/3*π*r₂³ = 324π
4/3π(r₁³ + r₂³) = 324π
r₁= 2r₂
4/3*π*[(2r₂)³ + r₂³) = 324π |:(4/3π)
8r₂³ + r₂³ = 243
9r₂³ = 243 |:9
r₂³ = 27
r₂ = ∛27
r₂= 3 cm

r₁= 2r₂
r₁= 2 *3cm
r₁= 6cm

V₁=4/3*π*r₁³ = 4/3 * π * 6³ = 4/3 * 216 * π = 288π cm³
V₂=4/3*π*r₂³ = 4/3 * π * 3³ = 4/3 * 27 * π = 36π cm³
1 5 1